Pelatihan Pemasaran Online Berbasis Marketplace Dalam Menghadapi Era New Normal - Evanita Evanita; Tutik Khotimah (Universitas Muria Kudus, 2022)
Billions of people in the world carry out social distancing and limit themselves in their activities almost entirely at home so that life becomes massive online or digital. However, since the new normal was enforced starting in June 2020, a number of companies have asked their workers to return to work in the office or workplace. On the other hand, many business people have survived by diverting sales via digital and utilizing the digital ecosystem in the form of startups during the pandemic. During the new normal, many products and services offered online were previously offline. In line with these services, the service team will conduct marketplace-based online marketing training in the face of the new normal era in Purwosari Kudus village considering that PKK women in Purwosari Kudus are also affected by the covid-19 pandemic. Based on the dedication that has been carried out, it can be concluded that the training can increase knowledge about various types and all differences in online sales facilities and improve trading skills and online sales turnover with the right strategies.